Teachers' Perceptions of Practices and Challenges of Innovating for the Inclusion of Special Needs University English Language Learners in Oman - Saleh Al-Busaidi; Victoria Tuzlukova (Sultan Qaboos University, 2018)
This study explored how English language teachers at Sultan Qaboos University's Center for Preparatory Studies in Oman perceive practices and challenges related to inclusive education and innovating in teaching English to visually impaired students. The study was carried out taking descriptive qualitative approach. Interviews with seven English language teachers were used to collect data. We asked them about both successful and challenging aspects of creating an inclusive language learning environment and using assistive technologies. We found that assistive technology is crucial to language learning of special needs students. The identified challenges include insufficient teachers' knowledge and expertise in inclusive education, lack of institutional focus of attention on systematic planning and material design for inclusion, novelty of the concepts of inclusive education and assistive technology among others. The results of the study indicate the need for targeted teacher training and professional development, and suggest that innovations in education and technology can be effectively used to shift practices and perspectives of English language teaching in the context of Oman to being universally accessible, equally usable, more inclusive and tailored to students' individual needs.